-9=6-3/5x

Simple and best practice solution for -9=6-3/5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9=6-3/5x equation:



-9=6-3/5x
We move all terms to the left:
-9-(6-3/5x)=0
Domain of the equation: 5x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
-(-3/5x+6)-9=0
We get rid of parentheses
3/5x-6-9=0
We multiply all the terms by the denominator
-6*5x-9*5x+3=0
Wy multiply elements
-30x-45x+3=0
We add all the numbers together, and all the variables
-75x+3=0
We move all terms containing x to the left, all other terms to the right
-75x=-3
x=-3/-75
x=1/25

See similar equations:

| 2x-2=39 | | -(x=4)-28 | | 3(7x-9)-19x=—15 | | 7x=8x+72 | | -7t+9=-5t-9 | | x*0.16=106 | | x+1+4=-9 | | r+13/2=-3 | | -3(t-2)=-23 | | 12x4=10 | | 5(x+2)-3x=(2x+5) | | 5b÷9=3 | | 16-3t=3t+40 | | 12x44=10 | | 5x+11=2(x-5) | | 10+10x=-10 | | 2(a+3)=22 | | 2b÷5+3b4=3 | | 3(2x+6)=-37+7 | | 7x+33+8+90=180 | | -a-a=6 | | 4(1-x)+3x=3x-2(x+1) | | (2x+7)/3=9 | | 10x-5+3x=9-x | | 46=-3x-5 | | 4x-5-+9=5x-9 | | 10x+45+6x+8x+3=360 | | x+3+2x+x=3(x+2) | | 6n-1=18 | | 2m=–9+3m | | -2(x–3)=30 | | 2x+3+3x+5=38 |

Equations solver categories